Bridging gaps between policies for sustainable markets and market practices. Issue 2 (13th June 2016) - Mattsson, Lars-Gunnar
Abstract : Purpose: – The problem addressed is how policies to promote sustainable development may be implemented in market practice. The purpose of this paper is to present a conceptual framework on which further research on sustainable market practice can be based. Design/methodology/approach: – Literature and conceptual analysis as regards sustainable development and policies to promote sustainable markets. Frameworks from theorizing about markets and about institutions. Findings: – The context of policy initiatives aiming at sustainable development is characterized by substantial heterogeneity and is inherently conflictual and multidimensional. Stakeholders, NGOs, governments as well as market actors are involved in policy processes. A market practice perspective is suggested. Specific issues for research are how policy practice interacts with market practice and how sustainable markets actually perform sustainable development over time and space. Practical implications: – Implications for how policy actors and market actors might act to bridge the gap by awareness of market shaping process in market practice. Originality/value: – Contribution to holistic understanding of links between policies, market practice and sustainable development.